Diversidad y estructura genética de la danta Centroamericana (Tapirus Bairdii) en el noroeste de la cordillera de Talamanca y en el corredor biológico Tenorio-Miravalles, Costa Rica - Delgado Carazo, Juan Carlos (2023)
Tapirus bairdii is the largest terrestrial herbivore living in Mesoamerica, distributed from southern Mexico to northwestern Colombia. Tapirs play relevant ecological roles as seed dispersers and nutrient cycling redistributors and modulators, among other ecosystem services provided. However, T. bairdii is endangered throughout its current range. The genetic study of the Central American tapir was declared a priority in the 2005 Tapir Specialist Group action plan, but few investigations exploring the genetics of T. bairdii have been published to date. We used invasive (blood, tissue, pulled out hairs) and non-invasive (feces, fallen hairs) samples and a set of seven microsatellite loci to describe the genetic diversity and structure of three a priori defined populations: Cerro de la Muerte (CM), Herradura-San Jerónimo (H-SJ) and Tenorio-Miravalles (TM) of wild tapirs from two high-biodiversity regions in Costa Rica: the Northwest of Talamanca Mountain Range (NWT) and Tenorio-Miravalles Biological Corridor (TMBC). We confirmed the presence of tapir-specific DNA in the collected samples by sequencing a fragment of 114-148 bp of cytb gene. We found moderate levels of genetic diversity (Ho=0.52) when analyzing the whole Costa Rican metapopulation. Our estimates of diversity by population ranged in the middle of previous reports from other populations of the species (Ho= 0.46-0.58). We found significant genetic structure among NWT and TMBC region (G’ST Nei=0.0587; p<0.001) and among the three populations using FST and G-Statistics. AMOVA analysis found significant genetic structure among NWT and TMBC regions (ϕCT=0.0602; p<0.001) and marginal genetic structure among populations (ϕSC=0.0479; p<0.05). Bayesian analysis of genetic clusters (K) grouped individuals into K=2, suggesting a similar configuration of individuals as the regional stratification did. The weak genetic structure between members of H-SJ and TM, plus the clear differentiation of CM and TM, suggest a strong putative pathway of gene flow from TM to H-SJ through the Atlantic slope, its protected areas and connectivity routes, whilst a weak putative pathway of gene flow from TM to CM through the Pacific slope is suggested. We recommend the inclusion of non-invasive samples in more population genetics studies, especially through the collaboration with local communities coexisting with wildlife as a strategy to offset the generalized lack of information about neotropical wildlife species. Using this approach, we achieved to collect, process, and analyze the highest number of samples reported to date for any American tapir species using microsatellite markers.